2014
DOI: 10.1007/s00018-014-1627-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperones are nanomachines that catalytically unfold misfolded and alternatively folded proteins

Abstract: By virtue of their general ability to bind (hold) translocating or unfolding polypeptides otherwise doomed to aggregate, molecular chaperones are commonly dubbed “holdases”. Yet, chaperones also carry physiological functions that do not necessitate prevention of aggregation, such as altering the native states of proteins, as in the disassembly of SNARE complexes and clathrin coats. To carry such physiological functions, major members of the Hsp70, Hsp110, Hsp100, and Hsp60/CCT chaperone families act as catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 163 publications
(194 reference statements)
0
85
0
1
Order By: Relevance
“…The phenogram of all FCBP sequences was derived from multiple sequence alignment as described in BMethods.^These sequences are exclusively eukaryotic, and the clusters are marked as these examples are small in number, I realized that a multiple alignment to find immunophilin-specific TPR consensus will be less useful than searching for specific residues known to function in protein-protein interaction. Among the TPRinteracting proteins that have been studied in detail are the heat shock proteins 70 and 90 (Hsp70 and Hsp90), which also act as chaperones (Mattoo and Goloubinoff, 2014). Both are also ubiquitous proteins with highly conserved sequence.…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…The phenogram of all FCBP sequences was derived from multiple sequence alignment as described in BMethods.^These sequences are exclusively eukaryotic, and the clusters are marked as these examples are small in number, I realized that a multiple alignment to find immunophilin-specific TPR consensus will be less useful than searching for specific residues known to function in protein-protein interaction. Among the TPRinteracting proteins that have been studied in detail are the heat shock proteins 70 and 90 (Hsp70 and Hsp90), which also act as chaperones (Mattoo and Goloubinoff, 2014). Both are also ubiquitous proteins with highly conserved sequence.…”
Section: Gammaproteobacteriamentioning
confidence: 99%
“…The electrostatic interactions formed between Spy and the client protein are a central component of this mechanism. Not only do they enhance the client binding rate and therefore kinetically prevent protein aggregation, they also help keep the client protein bound while it folds and hence eliminate the need for pre-native client release, a requirement that was previously considered essential for the successful folding of clients by chaperones (8,36). Loose client binding has been postulated to be important for chaperone-mediated client folding (37,38).…”
Section: Spymentioning
confidence: 99%
“…Further investigation suggested that the bacterial Hsp70 homologue, DnaK, specifically disrupted tertiary contacts while enabling local structure formation (87). Similarly, Hsp70s can unfold misfolded or even folded proteins through selectively binding to conformations that transiently expose hydrophobic binding motifs, shifting the folding equilibrium to more unfolded conformations and thereby remodeling the folding energy landscape (36,78,88). However, biophysical studies have also suggested that the lid subdomain and its flexible tail can adopt several different conformations to accommodate bulkier folded segments of proteins, allowing Hsp70 to bind not just unfolded polypeptide stretches but also folding intermediates and even near-native conformations, potentially using other binding modes (83,89,90).…”
Section: Hsp70mentioning
confidence: 99%
“…This question has been particularly challenged by the discovery of molecular chaperones in 1987. These molecular chaperones are nanomachines that catalytically unfold misfolded and alternatively folded proteins [64] . Molecular chaperones and their associated co-chaperones are essential in health and disease as they are key facilitators of protein folding, quality control and function.…”
Section: Protein Folding In the Cellmentioning
confidence: 99%